Five new species of Qadria Mahmood (Hemiptera: Cicadellidae: Typhlocybinae) from China - Song, Yue-Hua; Li, Zi-Zhong (Zootaxa, 2014)
Five new leafhopper species, Qadria bannaensis, Q. daliensis, Q. dongfanga, Q. guiyanga and Q. cucullata spp. nov. from Yunnan, Hainan and Guizhou Prov. of China are described and illustrated, and a key to all species of the genus Qadria is provided.